Clinical distinctions and pathogenic implications of type 1 autoimmune hepatitis in Brazil and the United States - Czaja, Albert J.; Souto, Enrico O.; Bittencourt, Paulo L.; Cancado, Eduardo L.R.; Porta, Gilda; Goldberg, Anna Carla; Donaldson, Peter T. (Journal of hepatology, 2002)
Background/Aims: Type 1 autoimmune hepatitis has a strong genetic predisposition that varies among different ethnic groups. Our aims were to determine if the clinical manifestations differed between patients with type 1 autoimmune hepatitis from Brazil and the United States and if classical disease could be associated with region-specific susceptibility markers. Methods: The clinical manifestations and genetic risk factors of 161 patients from the United States were compared to those of 115 patients from Brazil. Results: The patients from Brazil had earlier disease onset, lower frequency of concurrent immune diseases, higher serum levels of aspartate aminotransferase and γ-globulin, greater occurrence of smooth muscle antibodies, and lower frequency of antinuclear antibodies than the patients from the United States. Human leukocyte antigen (HLA) DR13 and DRB1*1301 occurred more commonly in the Brazilian patients and HLA DR4 less often. Normal subjects from each country had similar frequencies of HLA DR13 and DR3. Conclusions: Type 1 autoimmune hepatitis in Brazil has different features at presentation than the disease in Caucasoid patients from the United States, and it is associated with HLA DR13. Background populations in each country have similar frequencies of HLA DR13 and DR3, and region-specific etiologic factors may determine the HLA association.